086 An unexpected cause of ophthalmoplegia and areflexia: the pupils have it. (23rd August 2021) - Qiu, Jessica; Vien, Albert; Hannaford, Andrew; Ferguson, Patricia; Hamidi, Mohammad; Vaidya, Amit; Henderson, Andrew
Abstract : Introduction: We describe a case of botulism and its differentiation from acute neurological presentations. Case: A 35 year-old man presented with dysphagia, subjective jaw numbness, dyspnoea and vertigo. He denied alcohol intake but had injected methamphetamines and developed symptoms shortly after. 48 hours post-injection, he was drowsy and developed a complete internal and external ophthalmoplegia, an absent gag reflex with slow tongue movements and facial diplegia with sparing of distal muscle groups. His reflexes were initially present but became absent five hours later. There were no sensory or cerebellar findings. Blood cultures were taken given his history of intravenous drug use. Neuroimaging did not note the presence of a posterior circulation infarct. A lumbar puncture did not demonstrate cytoalbuminological dissociation, and antibody testing for myasthenia gravis and Guillain Barre Syndrome variants were negative, although he was commenced on empirical IVIg prior to these results. He required intubation on day three of admission due to hypoxia secondary to aspiration but needed minimal ventilatory support. Neurophysiological findings were consistent with a presynaptic neuromuscular junction disorder. Blood cultures noted clostridium botulinum with detection of clostridium botulinum toxin B. Antitoxin was administered on day four of presentation with slow but gradual improvement in his neurology and he was extubated on day 16. Conclusion: Acute causes of bilateral ophthalmoplegia include Wernicke's encephalopathy, Miller-Fisher Syndrome (MFS) variant of Guillain Barre Syndrome, brainstem stroke, myasthenia gravis and botulism. Of these, only MFS and botulism will cause both internal and external ophthalmoplegia.